Interactions between carbon impurities and defects produced by proton irradiation in α-iron - Apostolopoulos, G.; Lukianova, V.; Kotsina, Z.; Lagoyannis, A.; Mergia, K.; Harissopulos, S.; Messoloras, S. (HNPS Advances in Nuclear Physics, 2019)
Resistivity recovery experiments are performed on α-Fe and an Fe - 220 at. ppm C alloy after 5 MeV proton irradiation at cryogenic temperature of 50 K. By comparing the recovery spectra of pure Fe and the Fe-C alloy we are able to resolve the effect of carbon atoms on the point defect kinetics. It is observed that carbon interacts with both interstitial and vacancy type of defects and delays their annihilation. At temperatures above 500 K the formation of carbides reduces the resistivity of the alloy.